Genetic Divergence in Pod and Seed Traits of Pongamia pinnata (L.) - Singh, A. K.; Majidwani, Afaq (Indian Forester, 2016)
Pongamia pinnata is a medium-sized fast growing leguminous nitrogen fixing tree commonly known as Karanj. It is an excellent multipurpose tree with each and every part of the tree having specific use. Thirty Candidate Plus Trees (CPTs) of P. pinnata were selected from 30 different locations in Uttar Pradesh for the study of genetic divergence in pod and seed characters. The eight Principal Component (PCs) explained large portion (97.12%) of the total variation. The study revealed that the cluster analysis performed on the scores of the first eight PCs resulted into five clusters with cluster IV comprised highest number of ten candidate plus tree followed by cluster II, III, V and I having 7, 7, 5 and 1 CPTs, respectively. Seven PTs in cluster II (S2, S3, S13, S22, S23, S26 and S27) had high mean values and combination of desirable traits and can be directly selected for further genetic improvement programme.